On Historical Specifics of Moral Values - Meškauskas, Eugenijus (Problemos, 1979)
The problem of interrelation between the historical and the common to all mankind is observed in the article. An opinion is advanced that the common to all mankind does not constitute an independent element but is rather a definite aspect of this content.